ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO FUNDING RATIO (LFR) DAN BEBAN OPERASIONAL PADA PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA BANK PEMBANGUNAN DAERAH - Edison, Millen A'anisa Insani Sanra; Muchlis (Ibs Press, 2025)
The purpose of this study was to determine the effect of Capital Adequacy Ratio (CAR), Loan to Funding Ratio (LFR) and Operational Expenses on Operational Income (BOPO) on Return On Assets (ROA) at Regional Development Banks. Purposive Sampling was chosen as the sampling method in this study. The population in this study were 26 regional development banks in Indonesia for the 2014-2019 period. The method in this research uses multiple linear regression analysis method with a significance level of 5%. The hypothesis in this study is based on previous research and various other supporting theories that are processed using Eviews-9. The results of this study indicate that the bank's Capital Adequacy Ratio (CAR) has no effect on the Return on Assets (ROA) for the Regional Development Bank industry, the bank's Loan to Funding Ratio (LFR) has no effect on the Return On Asset (ROA) for the Regional Development Bank industry Operational Costs to Operational Income (BOPO) of banks have a significant effect with a negative relationship to Return On Assets (ROA) for the Regional Development Bank industry.